Case Report: A novel de novo variant of COL1A1 in fetal genetic osteogenesis imperfecta - Mai, Qiuyan; Han, Ruining; Chen, Yinlong; Shen, Ke; Wang, Shimin; Zheng, Qingliang (Frontiers in Endocrinology, 2023)
Objective: Osteogenesis imperfecta (OI) is a rare genetic disease. The clinical severity is heterogeneous. The purpose of this study was to investigate the genetic characteristics of a fetus with OI by whole exome sequencing (WES), and to identify the cause of the disease.In this study, a fetus with osteogenic dysplasia was referred to our hospital. DNA was extracted from aborted fetal tissue and peripheral blood of the parents. To identify the pathogenic genes, we conducted the trio-WES using the DNA. A de novo variant in the COL1A1 gene is suspected to be the cause of OI phenotype. We used Sanger sequencing for validation and various bioinformatics methods (including SIFT, PolyPhen2, Mutation Taster, conservative analysis, SWISS Model, glycosylation sites prediction, I-Mutant2.0) for analysis.Results: Both WES and Sanger sequencing identified a novel de novo variant of COL1A1 (c.1309G>A, p. Gly437Ser) in fetus with OI. Bioinformatic analysis showed that the affected residue p. Gly437 was highly conserved in multiple species and predicted that the variant was deleterious and may have an impact on protein function. This variant is present in highly conserved glycine residues of Gly-X-Y sequence repeats of the triple helical region of the collagen type I α chain, which may be the cause of OI.This study revealed that the c.1309G>A (p. Gly437Ser) variant in the COL1A1 gene may be the genetic cause of fetal OI in this case. The discovery of this variant enriched the variation spectrum of OI. WES improves the accurate diagnosis of fetal OI, and doctors can provide patients with appropriate genetic counseling.